Enhancing counseling services quality through technology-based student problem identification training - Indriyana Rachmawati; Agus Triyanto; Diana Septi Purnama; Tampi Prehadini (Universitas Muhammadiyah Magelang, 2024)
Guidance and counseling teachers must adapt to technological advancements to effectively deliver assistance services, including assessment. To streamline student support, these educators need to enhance their ability to provide services. This community service aims to improve guidance and counseling teachers' skills in assessing counselee problems using information technology-based models within schools. The process involves determining training needs, conducting training, and evaluating its impact. This initiative successfully enhanced teachers' capacity to accurately identify student issues through technology, leading to more targeted interventions.